Mendidik dengan Empati: Menumbuhkan Kesadaran HAM di Kalangan Pelajar - Resi, Reynathan Maulana; Putra, Bayu Pramana; Amanda, Ade Putra; Safardianur, Muhammad Rizki; Zakin, Kevin Okta; Sunaryo, Sunaryo (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Program pengabdian bertajuk